ANIMALS AND THE [ORTHODOX] CHRISTIAN FAITH - Stojanovic, Natasa (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
This paper considers the relation existing between animals and the orthodox [Christian] faith, particularly the one propagated by the Serbian Orthodox Church. The research has been conducted with the aim of acquiring a deeper knowledge of the bond connecting animals and the Orthodoxy, and to establish whether the Serbian Orthodox Church promotes animal welfare with its attitude toward animals, and further, whether its action suggests the recognition of certain rights to animals. For the purpose of this paper, the following methods are used: sociological, legal ad dogmatic, and historical and critical methods.The conducted research shows that the Serbian Orthodox Church has no an official stand towards animals; therefore, the relation referring to animals and the orthodox [Christian] faith cannot be precisely determined in Serbian spiritual climate. What is certain it that orthodox priests, under the influence of the canons of the Holy Scriptures, formally advocate for the respect and care of animals and condemn any cruel treatment of them. At the same time, love for animals must be moderate and never above love for God and neighbours. As the orthodox faith does not prohibit the use of meat and fish in the diet, and does not consider killing animals an immoral act, obviously, the Serbian Orthodox Church does not advocate for the recognition of rights to life of animals, thus the recognition of their legal subjectivity.A twelve-year application of the Law on Animal Welfare in the Republic of Serbia has shown that many factors prevent a more quality protection of their welfare. The Serbian Orthodox Church contributes to it to a “great” extent, not promoting the protection of animals and a more humane treatment with its acts and actions, particularly towards abandoned animals.
Keywords: animals; Holy Scriptures of the Old and New Testament; Orthodoxy; Serbian Orthodox Church